MOR2 hydrology field data - Venable, Niah B.H.; Fassnacht, Steven R.; Jigjisuren, Odgarav; Jamiyankhuyag, Sukhbaatar (Colorado State University. Libraries, 2020)
This record contains tables with location and measurements data from hydrologic (streamflow) work performed in Summer 2012 by S.R.Fassnacht, Niah B.H. Venable, Odgarav Jigjisuren and Sukhbaatar Jamiyankhuyag.
Warner College of Natural Resources